Предмет: Математика,
автор: tiktoker87
4х – 2 +3х = 2х + 63
− 8х – 17 = -х – 10
−3(3b + 1) +12 = -12
-2(у + 3) = 21 – 3у
2(-2 + у) = 21 – 3у
−3(2 – 5х) = − 6(-х - 3) – 6
– 4,92а – (0,08а + 5,12) = − 0,88 –а
у+0,89–(1,08у + 5,07) = 3,92у
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
1) б) 6х – 2 = 2х + 6
в) 11 + 7х = 55 + 3х
г) − 8х + 17 = 3х + 83
2)а) 5(2 + у) = 4 – 3у
б) −2(3b + 1) – 14 = 8
в) −3(2 – 5х) = 6(х + 3) – 6
г) – 3,92у – (1,08у + 5,07) = − 0,89 – у
tiktoker87:
Спасибо большое
Похожие вопросы
Предмет: Русский язык,
автор: нина137
Предмет: Английский язык,
автор: Zhanye200526
Предмет: Окружающий мир,
автор: матвей20052
Предмет: Английский язык,
автор: MikyYano1
Предмет: Қазақ тiлi,
автор: zere08032006